Optimizing Human Resources Management: Government's Crucial Role In Enhancing Education Resources In Indonesia - Wildan Nuryanto, Uli; Basrowi, Basrowi; Quraysin, Icin; Pratiwi, Ika (Edukasi Islami: Jurnal Pendidikan Islam, 2023)
Education is an important foundation in building the future of a nation. In the Indonesian context, the government has a significant role in ensuring access, quality and relevance of education throughout the region. This article explores the government's role based on the National Education System Law in improving education, focusing on policy implementation, curriculum, teacher training, as well as responses to the demands of the times and the needs of the global job market. This analysis also highlights the challenges faced and provides suggestions for improving the effectiveness of education policies. The results of the study show that the role of government is very important in improving human resources in the field of education, because without improving the quality of educational resources, the quality of education will not be improved. In other words, the quality of education will be able to increase when the quality of teachers and education personnel is improved in terms of educational capacity, experience, informal education, and various other learning skills. Future researchers can conduct research by looking at the role of local government in improving the quality of learning processes and outcomes or the leadership aspects of school principals, school committees and school supervisors